2007
DOI: 10.1007/s11101-006-9051-z
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factors involved in terpenoid indole alkaloid biosynthesis in Catharanthus roseus

Abstract: Plants produce alkaloids, among others, to protect themselves against microbial infection, herbivore attack or ultraviolet irradiation. For man, alkaloid metabolism is the source of many natural products with useful applications, including pharmaceuticals. A major mechanism regulating alkaloid production in plant cells is the control of the transcription of the biosynthetic genes. Several transcription factors involved in the regulation of alkaloid biosynthesis genes have been isolated and studied. There are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 58 publications
1
52
0
Order By: Relevance
“…However, JA also induces the repressors ZCT and GBF, proteins that are known to inhibit the expression of TDC and STR (Memelink and Gantet, 2007). The emerging picture of the transcriptional control of TIA biosynthesis suggests the simultaneous induction of activators and repressors by elicitors and developmental signals.…”
Section: Overexpression or Repression Of Crwrky1 Affects The Accumulamentioning
confidence: 99%
See 2 more Smart Citations
“…However, JA also induces the repressors ZCT and GBF, proteins that are known to inhibit the expression of TDC and STR (Memelink and Gantet, 2007). The emerging picture of the transcriptional control of TIA biosynthesis suggests the simultaneous induction of activators and repressors by elicitors and developmental signals.…”
Section: Overexpression or Repression Of Crwrky1 Affects The Accumulamentioning
confidence: 99%
“…The activator, ORCA3, apparently pushes the flux toward the vindoline and catharanthine pathways. Previous work has demonstrated that ORCA3 activates the vindoline pathway enzyme, tabersonine 16-hydroxylase (Memelink and Gantet, 2007), and when sufficient precursors from the terpenoid pathway become available, as the result of G10H overexpression, ORCA3 preferentially activates the catharanthine pathway (Wang et al, 2010a). Conversely, CrWRKY1 induces the serpentine pathway by repressing ORCA3 and activating the serpentine branch genes, including the putative peroxidase gene converting ajmalicine to serpentine.…”
Section: Overexpression or Repression Of Crwrky1 Affects The Accumulamentioning
confidence: 99%
See 1 more Smart Citation
“…Various TFs were shown to bind the STR promoter, including CrMYC1, the putative ortholog of MYC2; CrZCT1 to CrZCT3, homologs of STZ/ZAT10 and AZF2; and CrORCA1 to CrORCA3, encoding AP2/ERF proteins homologous to ORA47 (35). It is tempting to speculate that proteins such as MYC2, ORA47, STZ/ZAT10, AZF2, and perhaps other earlyresponsive Arabidopsis TFs regulate not only early MeJA responses such as JA biosynthesis, but also later responses, such as activation of phenylpropanoid metabolism.…”
Section: M-phase Gene Repressionmentioning
confidence: 99%
“…The biosynthesis of vinblastine involves more than 20 enzymatic steps, nine of which are now well characterized at the enzyme and gene level, and several regulatory genes of the pathway (ORCAs) have also been cloned. However, considerable parts of the pathway remain relatively hypothetical, and even enzymatic characterization is still lacking for many steps (for review, see Hilliou et al, 2001;El-Sayed and Verpoorte, 2007;Loyola-Vargas et al, 2007;Memelink and Gantet, 2007).…”
mentioning
confidence: 99%